PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN (Studi Pada Perusahaan Manufaktur Sektor Plastik dan Kemasan yang terdaftar di Bursa Efek Indonesia) - Saputra, Dodi; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The aim of this study to determine the influences of Firm Size, Profitability and leverage toward Companies Value of Plastic and Packaging which is listed on Indonesia Stock Excange. Ratio of the size of the campany is used as the independent variable is the natural lagarithm of total asset(Ln total asset. Profitability ratio which is used as independent variabel are return on equity (ROE) and return on investment (ROI) and and Leverage ratio were use as independent variables is Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER). While the value companies as dependent variabel measured by ratio price book value (PBV).In this study, the data where financial report and annual report. The sampling taken by purposive sampling, the sample are 6 from companies in plastic and packaging which is listed on Indonesia Stock Excange. Analysis techniques in this study are simple linear, double linear, determinate coefficient, test t(partial), and test F(simultan). Data analysis was used analysis linear agression with the help of software SPSS 21.The results showed that the size of the company partially (t test) significantly affect the value of the company. Profitability has no significant effect on firm value. While the leverage also has no significant effect on firm value. The result of simultaneous research (F test) showed no significant influence between company size, profitability and leverage together to the value of the company in plastic and packaging sector listed in Indonesia Stock Exchange.Keyword: firm size, Profitability, leverage, The Companies Value